Crosstalk between plasmid vegetative replication and conjugative transfer: repression of the trfA operon by trbA of broad host range plasmid RK2. - Jagura-Burdzy, G (1992)
Previous deletion and complementation analysis has indicated that the region between trfA and kilBI (trbB) encodes trans-acting factor, designated trbA, required for conjugative transfer of broad host range plasmid RK2. In analysing the nucleotide sequence of this region we have discovered a gene encoding a 12 kDa polypeptide. The predicted amino acid sequence of this protein shows similarity at its C-terminal to KorA from the central control operon of RK2 and at its N-terminal to immunity repressor protein from phage phi 105 of Bacillus subtilis as well as the Sin protein of B. subtilis which regulates alternate developmental processes including sporulation, motility and competence. We show that TrbA represses transcription of both trfA (vegetative replication) and kilBI (trbB) (required for conjugative transfer and whose product has similarity to ComG, required for competence of B. subtilis) and may help to coordinate expression of both sets of functions. This region has similarities to some temperate bacteriophage immunity regions in modulating divergent transcription required for alternative means of propagation.